2008
DOI: 10.1007/s10228-008-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niches of thirteen damselfishes (Pomacentridae) at the Grand Récif of Toliara, Madagascar

Abstract: The damselfishes, with more than 340 species, constitute one of the most important families that live in the coral reef environment. Most of our knowledge of reef-fish ecology is based on this family, but their trophic ecology is poorly understood. The aim of the present study was to determine the trophic niches of 13 sympatric species of damselfishes by combining stable isotope (d 15 N and d 13 C) and stomach content analyses. Isotopic signatures reveal three main groups according to their foraging strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 31 publications
4
84
0
Order By: Relevance
“…Specifically, zooplankton was sampled with a 250-µm net towing at 2 m depth above reefs. This sampling method was replicated three times and is similar to the technique used to study the niche partitioning of damselfishes in Madagascar (Frédérich et al 2009). …”
Section: Sampling and Collection Of Ecological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, zooplankton was sampled with a 250-µm net towing at 2 m depth above reefs. This sampling method was replicated three times and is similar to the technique used to study the niche partitioning of damselfishes in Madagascar (Frédérich et al 2009). …”
Section: Sampling and Collection Of Ecological Datamentioning
confidence: 99%
“…pelagic feeders, benthic foragers and an intermediate group Frédérich et al 2013Frédérich et al , 2016a. Several field observations also suggested a strong link between diet, habitat use and social behaviour in Pomacentridae (Emery 1973;Frédérich et al 2009), but they only constitute a qualitative assumption. The analysis of quantitative data is therefore needed to formally establish these correlations.…”
Section: Introductionmentioning
confidence: 99%
“…They display remarkable diversity related to habitat preferences, feeding habits and behaviors (Robertson and Allen 2008). For example, some herbivorous damselfishes are highly territorial and manage their own algae farm (e.g., Stegastes) (Lobel 1980;Ceccarelli 2007) when several planktivorous damselfishes (e.g., Chromis, Abudefduf) are schooling species feeding in the water column (Emery 1973;Frédérich et al 2009). All formerly studied damselfishes show pectoral fin swimming (MPF), except some species belonging to the genera Plectroglyphidodon, Dischistodus and Stegastes which use both pectoral and caudal fins for swimming (Fulton 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are three main trophic guilds in damselfishes: (1) the pelagic feeders that feed mainly on planktonic copepods, (2) the benthic feeders that mainly graze filamentous algae and (3) an intermediate group including species that forage for their prey in the pelagic and the benthic environments in variable proportions (e.g. planktonic and benthic copepods, small vagile invertebrates and filamentous algae) (Frédérich et al, 2016(Frédérich et al, , 2009. A study on a zooplanktivorous species, Amphiprion clarkii (Bennett, 1830), showed that the c-md mechanism is never used to capture elusive prey (Olivier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%